2023
DOI: 10.1039/d2rp00110a
|View full text |Cite
|
Sign up to set email alerts
|

Guided inquiry-based learning in secondary-school chemistry classes: a case study

Abstract: Guided inquiry-based learning has been shown to be a promising method for science education, though, despite its advantages, it is rarely used in chemistry teaching in Hungary. One of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…The importance of developing problem-solving skills in students is emphasized in the work of several authors, e.g., Lesh and Zawojewsky [6], who claim that a developed problem-solving ability facilitates further education, successful involvement in society, and is necessary for a range of personal activities as well. As confirmed by other authors [7][8][9][10], inquiry-based teaching has shown to be a promising method of education.…”
Section: -Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…The importance of developing problem-solving skills in students is emphasized in the work of several authors, e.g., Lesh and Zawojewsky [6], who claim that a developed problem-solving ability facilitates further education, successful involvement in society, and is necessary for a range of personal activities as well. As confirmed by other authors [7][8][9][10], inquiry-based teaching has shown to be a promising method of education.…”
Section: -Introductionmentioning
confidence: 58%
“…In the inquiry-based approach, a crucial role is played by teachers, whose ways and principles of teaching have an impact on students. As research findings show [8,[17][18][19], teachers lack competencies in the field of implementing inquiry-based activities, and international knowledge and experiences point to the fact that teachers' professional preparedness has a significant impact on the quality of education. Teachers must be well prepared for any changes to be introduced, and therefore, in the case of those who did not receive sufficient undergraduate training in the field, in-service teacher training opportunities focused on innovative strategies and methods, as well as their implementation, should be created.…”
Section: -Purpose Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…When planning activities, the cost in terms of time and money remained a consideration. If these constraints were ignored, it is unlikely that the tried and tested activities would be suitable and widely usable after the research project is completed (Boesdorfer and Livermore, 2018;Orosz et al, 2022).…”
Section: Conditions Of Combustionmentioning
confidence: 99%